Assessing NASA-POWER Precipitation Product in Predicting Surface Flow: Lower Jhelum River Case Study - Muhammad Raza Khalid; Shehroz Ahmed; Abdullah Abdullah (Air, Soil and Water Research, 2024)
The Lower Jhelum River watershed has variable topography (i.e. northern mountains and southern plains) and a subtropical climate with hot summers and cool winters. This emphasized the extensive use of state-of-the-art POWER reanalysis precipitation product rather than gauge estimates for hydrological investigations (modeling rainfall runoff, floods, and droughts etc.). To understand the consistency and potential of the precipitation values from both sources, the primary objective of this study was to establish a relationship between POWER data and rain gauge data by utilizing 13 rain gauge stations present in the catchment. While analyzing the rainfall data, a relatively weaker linear association ( R ), ranging from .6, .68 to .78, was found between the ground-based observatories and the POWER product especially for the arid and semi-arid regions. For the mountainous part, covering a wide glacial range, POWER product showed a better match with ground-based observatories that is, R value ranging from .78, .88 to .91. The simulated stream flow results by integrated HEC-HMS model showed that the POWER product can become a good asset in developing the weather data for those areas where the rain gauges are either absent or inaccessible.